Development and validation of next-generation sequencing panel for personalized Helicobacter pylori eradication treatment targeting multiple species - Min, Byung-Joo; Seo, Myung-Eui; Bae, Jung Ho; Kim, Ji Won; Kim, Ju Han (Frontiers in Cellular and Infection Microbiology, 2024)
IntroductionThe decreasing Helicobacter pylori eradication rate is primarily attributed to antibiotic resistance, and further exacerbated by uniform drug administration disregarding a host’s metabolic capability. Consequently, applying personalized treatment based on antibiotic resistance-associated variants and the host’s metabolic phenotype can potentially increase the eradication rate.MethodA custom next-generation sequencing panel for personalized H. pylori eradication treatment (NGS-PHET) was designed which targeted the regions for amoxicillin, clarithromycin, metronidazole, tetracycline, and levofloxacin-resistance in H. pylori and human proton-pump inhibitor (PPI) metabolism. The libraries were constructed following customized methods and sequenced simultaneously. The customized framework criteria, grounded in previously reported antibiotic resistance associated variants and the host’s PPI metabolism, was applied to the NGS-PHET results and suggested a personalized treatment for each subject, which was validated through each subject’s actual eradication outcome.ResultsBoth previously reported and novel variants were identified from H. pylori sequencing results. Concurrently, five CYP2C19 homozygous extensive metabolizers and three CYP3A4 intermediate metabolizers were identified. Among the total of 12 subjects, clarithromycin triple therapy was suggested for five subjects, bismuth quadruple therapy was suggested for six subjects, and rifabutin triple therapy was suggested for one subject by following the customized framework criteria. The treatment suggestion for nine of the 12 subjects was consistent with the treatment that each subject achieved eradication with.DiscussionApplying the methodology using the NGS-PHET and customized framework helps to perform eradication treatment quickly and effectively in most patients with antibiotic-resistant H. pylori strains, and is also useful in research to find novel antibiotic-resistance candidates.